The paradox of local abundance: mining and well-being at risk. The case of Zacatecas - RAMÍREZ HERRERA, Mariana; FLORES DE LA TORRE, Juan; GONZÁLEZ DÍAZ, Anthony (Utopía y Praxis Latinoamericana, 2023)
In Mexico, the State policy in favor of mining extractive -based on the idea that the exploitation of the subsoil will generate sufficient resources to achieve well-being and progress- has caused irreparable environmental damage to the mining populations, generating a paradox of abundance at the local level. This situation is analyzed here in economic, social, and environmental terms in the mining community of Valdecañas, in Fresnillo, Zacatecas; corroborating the environmental impact of mining, the scarce resources it generates for the economy, and the risk it has on the well-being and health of people.